Metformin inhibition of colorectal cancer cell migration is associated with rebuilt adherens junctions and FAK downregulation. Issue 11 (2nd April 2020) - Amable, Gastón; Martínez‐León, Eduardo; Picco, María Elisa; Nemirovsky, Sergio I.; Rozengurt, Enrique; Rey, Osvaldo
Abstract: E‐cadherin, a central component of the adherens junction (AJ), is a single‐pass transmembrane protein that mediates cell–cell adhesion. The loss of E‐cadherin surface expression, and therefore cell–cell adhesion, leads to increased cell migration and invasion. Treatment of colorectal cancer (CRC)‐derived cells (SW‐480 and HT‐29) with 2.0 mM metformin promoted a redistribution of cytosolic E‐cadherin to de novo formed puncta along the length of the contacting membranes of these cells. Metformin also promoted translocation from the cytosol to the plasma membrane of p120‐catenin, another core component of the AJs. Furthermore, E‐cadherin and p120‐catenin colocalized with β‐catenin at cell–cell contacts. Western blot analysis of lysates of CRC‐derived cells revealed a substantial metformin‐induced increase in the level of p120‐catenin as well as E‐cadherin phosphorylation on Ser 838/840, a modification associated with β‐catenin/E‐cadherin interaction. These modifications in E‐cadherin, p120‐catenin and β‐catenin localization suggest that metformin induces rebuilding of AJs in CRC‐derived cells. Those modifications were accompanied by the inhibition of focal adhesion kinase (FAK), as revealed by a significant decrease in the phosphorylation of FAK at Tyr 397 and paxillin at Tyr 118 . These changes were associated with a reduction in the numbers, but an increase in the size, of focal adhesions and by the inhibition of cell migration. Overall, these observations indicate that metformin targets multiple pathways associated with CRC development and progression. Abstract : The studies described in this paper indicate that metformin, a widely used antidiabetic drug, promoted the plasma membrane translocation and colocalization of E‐cadherin, β‐catenin, and p‐120 catenin at cell–cell contacts and the inhibition of focal adhesion kinase and ERK signaling as well as cellular migration inhibition in colorectal cancer‐derived cells.